Determinants of access to finance by Small and Medium Enterprises in Kajiado County - Dau, Joseph Kuer (Strathmore University, 2019)
In Kenya, private sector development remains critical for economic growth and development, particularly in creating jobs among unemployed Kenyan youths. The SME sector has grown in stature though it's riddled with myriad challenges among them financing despite the fact that this sector has so far employed 7.5 million youth which is 80% of the total persons employed in Kenya. The objective of the study was to find out the determinants of access to finance by small and medium enterprises in Kajiado County, Kenya. The specific objectives of the study included; determining the influence of borrowing firm's characteristics on access to finance among SMEs in Kajiado County, establishing the influence of product features on access to finance among SMEs in Kajiado County; finding out the influence of lender characteristics on access to finance among SMEs in Kajiado County. The study employed descriptive and inferential research design targeting 368 respondents comprising SME owners. The questionnaires administered to collect the research data have a response rate of 61.4% which is 226 of the target population. From the inferential statistics results, the study found that product features explain up to 70.6% of the variations in access to credit among the SMEs, firm characteristics explain up to 52.7% of the variations in access to credit while lender characteristics explain up to 19.2% of credit access by SMEs in Kajiado County. This study, therefore, recommends that given the role played by the SME sector in employment creation, there is a need for a concerted effort to focus on streamlining the access to credit policy among SMEs. And that management of financial institutions needs to establish frameworks that address key concerns on credit access. Commercial banks management enhancing management competencies in SME lending to customize product features rather than a size fit all SMEs. Such research will enable financial institutions to deliver products suiting women with such characteristics as grace periods, competitive interest rates, flexible loan periods, unnecessary hidden charges, social guarantees rather than tangible collaterals as well as the ability to graduate SME loans based on good credit history.
Submitted in partial fulfillment of the requirements for the award of a Master's in Business Administration (MBA) Degree